معنى الحياة عند مستخدمي مواقع التواصل الاجتماعي - زكري, نرجس; بوعيشة, أمال (جامعة الوادي - University of Eloued, 2020)
تهدف الدراسة الحالية إلى الكشف عن معنى الحياة عند مستخدمي مواقع التواصل الاجتماعي بجامعة محمد خيضر بسكرة، وتكمن أهمية الدراسة في كونها تمس فئة عريضة ضمن المجتمع وهم مستخدمي مواقع التواصل الاجتماعي، وكذا متغير حديث من متغيرات علم النفس الإيجابي وهو معنى الحياة، وقد قمنا بالدراسة على 90 طالب وطالبة أختيروا بطريقة قصدية وباعتماد المنهج الوصفي الاستكشافي، وتم تطبيق اختبار معنى الحياة لــ"هارون توفيق الرشيدي" 1996 والذي قام بتقنينه "بشير معمرية"، وذلك بعد التحقق من ملائمة الأداة للتطبيق على المجتمع المحلي بمنطقة بسكرة من خلال قياس بعض الخصائص السيكومترية له، ولتحقيق أهداف الدراسة قمنا بطرح التساؤلين التاليين: ما مستوى معنى الحياة لدى الطلبة الجامعيين من مستخدمي مواقع التواصل الاجتماعي؟ هل يوجد فروق بين الجنسين في إدراك معنى الحياة لدى الطلبة الجامعيين مستخدمي مواقع التواصل الاجتماعي؟ ومن خلال المعالجة الإحصائية لفرضيات الدراسة عن طريق الحزمة الإحصائية الطبعة20، تم التوصل إلى أن معنى الحياة إيجابي لدى مستخدمي مواقع التواصل الاجتماعي وهو بين المرتفع والمعتدل، وانه هناك فروق جوهرية بين الجنسين في معنى الحياة لصالح الذكور. Abstract: The objective of this study is to show the meaning of life for the Facebook site users at the University of Mohamed Khidr Biskra. The importance of the study lies in the fact that it includes a wide category within the community. Although a new positive psychology Variable "the meaning of life". 90 male and female who selected randomly for the study by adopting the descriptive exploratory approach. meaning of life test was applied by “Haroun Tawfiq AlRashidi” 1996, which was codified by “Basheer Maamariah”. Verifying tool convenience to apply on the local Biskra region community by measuring some of its psychometric properties, to achieve the studygoals the following questions were asked : What is the level of meaning of life among university students from Facebook users ? Are the regender difference son understanding the meaning of life for university students Facebook users? Through the study hypotheses statistical treatment by the statistical package SPSS edition 20, it was concluded that the meaning of life is positive for Facebook users, between high and moderate, and it exists fundamental differences between genders for the meaning of lif.
مقال
Keywords: معنى الحياة؛ مستخدمي مواقع التواصل الاجتماعي; The meaning of life; Facebook site users